How Should Athletes Coping With COVID-19: Focus on Severity and Psychological Support - Han, Qi; Li, Xueyang; Wang, Zhenghanxiao (Frontiers in Psychology, 2021)
Objective: Athletes are suffering from many uncertainties and hope to achieve the best possible position under the current circumstances of this global COVID-19 pandemic. Here, we aim to address the severity and psychological support for athletes with COVID-19. Methods: We extracted public data and news reports of the up-to-date first seven cases of elite athletes with COVID-19 confirmed in China and made psychological recommendations based on scientific evidence. Results: The severity and mortality in athletes tested positive to COVID-19 are mild and extremely low. The included cases from different sports are two soccer players, two athletes from ice hockey, and three from fencing. Here, we adapt well recognized psychological questionnaires and make it easy for athletes to use under COVID-19 pandemic, and also providing recommended psychological support. Conclusion: The severity and mortality in Chinese athletes contracted with COVID-19 are mild and low with zero death. Psychological support of any kind from nurses, team medical staff, psychologists, family, and friends through social media and telecommunication should be adopted and can be of great help.